Acoustic Environment of Urban Historical Places: A Case Study in Kastamonu, Turkey - Belkayalı, Nur; Kaymaz, Işıl (MDPI AG, 2021)
The general aim of this paper is to demonstrate the significance of the acoustic environment in urban historical places, which represent intangible cultural heritage, and to emphasize the need for the spaces to have their own unique acoustic environment depending on their characteristics. Both sound pressure level measurements and sound classifications were conducted in three urban historical places to emphasize their effect on the character of the area. Based on the data obtained, noise maps were created. The results of the study indicated that there was no change in sound sources due to the similarity of past and present usage types of the three selected historical areas, and that sound sources as an element of cultural heritage in the area were preserved and survived to the present day as a consequence. The type of use, intensity of use, structural-plant density, and climatic change were found to be effective in determining the acoustic environment character. The continuity of sound sources, which are among the elements that constitute the identity in historical places in particular and can be considered as cultural heritage elements, and the harmony of these sound sources for the intended use of the space are the factors that should be taken into account in spatial planning and design.
Keywords: sound; acoustic characteristics; urban landscape; cultural heritage; noise maps; 13. Climate action; 11. Sustainability; 15. Life on land